Mental Disorders, Personality Traits, and Grievance-Fueled Targeted Violence: The Evidence Base and Implications for Research and Practice. Issue 5 (3rd September 2018) - Corner, Emily; Gill, Paul; Schouten, Ronald; Farnham, Frank
ABSTRACT: This article aims to move away from intuitive appeals that link mental disorder with violence such as terrorism, mass murder, and other targeted violence. The article synthesizes the existing evidence base regarding the relationship between mental disorders and personality traits and (a) attitudinal affinities with violent causes, and (b) a number of violent behaviors (including mass murder and terrorism). The evidence base is mixed and the research focus changed across time: from simple and unempirical assertions of causation to an almost complete rejection of their presence to a finer grained and disaggregated understanding. Empirical research examining mental disorder in crime and violence highlights that the commission of such events is a complex synthesis of psychopathology, personal circumstance, and environment. The article concludes with several suggestions regarding future research and practice.